A delay and disruption tolerant transport layer protocol - Farrell, Stephen (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2008)
The area of delay-tolerant networking (DTN) is concerned with highly challenged networks in which application layer "sessions" commonly lack contemporaneous end-toend connectivity. For example, efforts to create networks involving Mars orbiters must deal with visibility constraints that mean that devices are not contactable for extended durations. Some wireless sensor networks, (where sensors are only occasionally contactable, for power management or location reasons), also impose similar networking challenges.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin